الأورام ما حول مجل فاتر: تشخيص وتدبير - قنجراوي أكثم; حاج قاسم فؤاد; نقولا عيسى (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في مشفى الأسد الجامعي في اللاذقية بين عامي 1999 – 2009، تضمنت 45 مريضاً (29 ذكراً, 16 أنثى) لديهم أورام ما حول مجل فاتر، وكانت نتائج الدراسة على النحو الآتي: كانت نسبة الذكور إلى الإناث 1.8: 1والعمر الوسطي للمرضى هو 58.12 سنة والعقد السادس هو المجموعة العمرية الأكثر توارداً, توضعت الآفات في رأس المعثكلة في حوالى 71% من المرضى والعرض الأكثر شيوعاً هو اليرقان. بلغت حساسية التصوير المقطعي المحوسب في كشف أورام ما حول مجل فاتر 72.09%. كان معدل العمل الجراحي الشافي 14.08% لأورام رأس المعثكلة و0% للقسم القاصي من القناة الجامعة و 0% للعفج و60% لمجل فاتر. كانت نسبة البقيا لمدة سنة عند المرضى المصابين بأورام رأس المعثكلة ولم يجر لهم عمليات جراحية شافية 10%. This study was carried out at Al-Aasad University Hospital in Lattakia between1999 and 2009, and included 45 patients (29 males,16 females) who had Periampullary carcinoma. The results were as follows. The ratio of males to female was 1.8 to 1, the median age of patients was 58.12 years, and the 6th decade was the most prevalent age group. Approximately, 70% of the lesions were located at the head of pancreas, and the most common symptom was Jaundice. The sensitivity of computerized tomography of Periampullary carcinoma was 72.09%; the curative surgery rate for lesions at the head of pancreas was 14.08%, and that of distal common bile duct, ampulla of vater, and duodenum was 0%, 60%, and 0%, respectively, The 1 year survival rate of patients non-operated on for cancer at the head of pancreas was 10%.